bahasa inggris - Ani Yoraeni Hasan; Hendra Ferdiana (Komunitas Dosen Indonesia, 2024)
Information system audits have an important role in an organization, namely they can help identify security risks that may be faced by the company's information system and ensure that the company complies with applicable information security standards and regulations. The problem faced is that there is no framework for knowing the extent to which the system is working properly. In conducting an information system audit, instruments are needed in the form of frameworks, principles or standards that have been determined by competent organizations in their field. COBIT 5 is a framework in the form of a collection of best practices related to IT governance that can be applied in information audit activities. Implementing an information system audit using COBIT 5 is carried out by collecting control documents and aligning them with COBIT 5 basic practices, then conducting an assessment on each selected domain based on existing control documents. In this study, the domains chosen were DSS and MEA with subdomains consisting of DSS1, DSS2, DSS3, DSS4, DSS5, DSS6, MEA1, MEA2. The research results show that the inventory transaction information system is at level 1 (performed process), meaning that the process in each selected domain has been implemented and is in accordance with its objectives. These results can be a reference for improving the governance of inventory transaction applications in particular and IT governance in general so that they are in line with the company's business objectives.